Takayasu’s arteritis - a summary of current, clinically relevant knowledge of the disease - Kłakowicz, Philip; Siedlak, Agnieszka; Kułakowska, Aleksandra; Lepczyński, Bartłomiej; Lechowski, Sebastian (Journal of Education, Health and Sport, 2023)
Takayasu’s disease, also known as pulseless disease or aortic arch syndrome, is a rare inflammation of the aorta and its branches, and sometimes the pulmonary arteries, which, according to studies, occurs most frequently in people from the Far East and Asian countries. In addition, its incidence is significantly higher in women, and the mean age of affected patients is 45.4 years [1]. The first official clinical case report of the disease by Shimizu and Sano appeared in 1951, while the name of the disease was proposed by Cassamise and Okuda in 1954 to honour the first clinician, Mikito Takayasu, who as early as 1908 presented a case of a young female patient with characteristic fundus lesions associated with pulse disturbances [2].